2016
DOI: 10.5539/jgg.v8n1p41
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Changes and Fragmentation Analysis in a Guinea Savannah Ecosystem: Case study of Talensi and Nabdam Districts of the Upper East region, Ghana

Abstract: Landcover change is an observed natural change dynamics at both the local and regional levels. However, its scales are exacerbated by human interaction with its natural environment. The study examines these spatio-temporal changes in landcover and the level to which the change is accompanied by fragmentation of the identifiable cover types in the Talensi and Nabdam districts in Northern Ghana. The research uses digital classification of Landsat satellite imagery for 1999 and 2007 to produce the cover types whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…A multi-method research approach was adopted in this study. This entailed the integration of qualitative and quantitative research methods since no single method can completely capture the relevant areas of the study ( Ampofo et al., 2016 ; Bryman, 2016 ). In this study, qualitative data collection tools such as observation and interviews were employed while measurement (quantities) of solid healthcare waste was the quantitative tool used.…”
Section: Methodsmentioning
confidence: 99%
“…A multi-method research approach was adopted in this study. This entailed the integration of qualitative and quantitative research methods since no single method can completely capture the relevant areas of the study ( Ampofo et al., 2016 ; Bryman, 2016 ). In this study, qualitative data collection tools such as observation and interviews were employed while measurement (quantities) of solid healthcare waste was the quantitative tool used.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported these methods of waste transportation in other towns and cities in Ghana [16] [37] and other developing countries [5]. , contaminate ground and surface water [38], release greenhouse gases and other air pollutants [20], damage ecosystems, and discourage tourism and other businesses [39].…”
Section: Waste Transportation and Final Disposal Methods In The Bawkumentioning
confidence: 99%
“…The other factors that militate against efficient solid waste management are poor financing capacity of local authorities, low technical capacity for planning and management of solid waste [16], weak enforcement of environmental regulations [12]. In view of this background information on the country, it appears that the development of an in-depth database on solid waste management situations in each district, municipal and metropolitan assembly in Ghana will help formulate and implement effective solid waste management policy in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have highlighted edaphic, topographic, climatic, and anthropogenic factors, among many other causal factors [33]. These studies have recommended that information associated with factors, such as habitat extent, landscape configuration, and habitat configuration regarding different plant species, must be collected timeously [26,[39][40][41][42]. This information allows the ongoing generation of LULCC maps and habitat maps essential for continuously monitoring landscape changes of national and international conservation significance [25].…”
Section: Land Cover Change Overviewmentioning
confidence: 99%